Pengaruh Pertumbuhan Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Property Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016 - Achmad Setya Nugraha; Maulana Yusup; Djadjun Juhara (Majalah Bisnis & IPTEK, 2018)
The value of the firm is investor’s perception towards the firms success level which is related to supply and demand that reflected the price of the stock. The high value of the firm will make the investors believe not only the present condition of the firm, but also the prospect of the future firm’s performance. Based on the previous relevant researches, there are some factors can influence the value of the firm, such as: decision of funding, dividend policy, investment decision, firm’s growth, leverage, profitability, firm’s size, etc. Some of the factors have relationship and influence towards the inconsistency value of the firm, so this research aimed to finding out the influence of firm’s growth (Total Assets Growth) and profitability (ROE) towards value of the firm (PBV) at property sector of Indonesia Stock Exchange. The population of this research was the property sector registered at Indonesia Stock Exchange from 2012 to 2016. To determine samples was using purposive sampling method with some fixed criteria such as: firms was listed at property real-estate sector before 2011, periodically released their financial report with representatives ratio used in this research and total 12 firms for samples. The data used was the secondary data which was obtained from MNC Securities program MNC Trade from 2012 to 2016. The analysis instrument is panel data regression and using EViews 9 for tool. This research shows both firm’s growth and profitability influence positive and significant with total 79.45%. It it recommended for the investor to look after the positive